The Effect of Macroeconomic Conditions on the Performance of Vietnamese Stock Market - Pham, Hien-Ly; Lin, Ching-Chung; Chan, Shih-Ju (Archives of Business Research, 2021)
Vietnam plays an important role in the global supply chain. As one of important emerging markets, many studies have focused on Vietnam-related issues. Vietnam established two stock markets in 2000s. The market performance becomes one of interesting issues to explore. This study is to investigate the impact of macroeconomic variables, including inflation rate, exchange rate, interest rate, imports, exports, and gold price, on Ho Chi Minh stock market. The study period is from July 2000 to October 2014. Using the monthly data collected from Vietnam General Statistic Office, IMF International Financial Statistics, and Ho Chi Minh stock exchange, the empirical findings of our regression model show that there exists a positive relationship for imports and gold price, while the relationships for exchange rate and interest rate are negative. No significant relationship has been found for the variables of inflation rate and exports.